ASUPAN SENG, KADAR SERUM SENG, DAN STUNTING PADA ANAK SEKOLAH DI PESISIR SEMARANG - Pramono, Adriyan; Panunggal, Binar; Anggraeni, Neni; Rahfiludin, Mohammad Zen (Jurnal Gizi dan Pangan, 2016)
The purpose of this study is to determine prevalence of at risk inadequate intake of dietary zinc, and to analyze differences of zinc serum level between dietary zinc quintile and stunting status. A cross sectional study was conducted to 70 school children (9-12 years) selected by simple random sampling. Height was measured by stadiometer and weight was measured using calibrated digital weight-scale. Zinc serum level was analyzed by Atomic Absorbance Spectrophotometry (AAS) method, and dietary intake of zinc and iron was obtained using semi-quantitative Food Frequency Questionnaire (FFQ). Data were analyzed using Anova test. Seventy percent subjects were at risk inadequate intake of dietary zinc based on Estimated Average Requirement (EAR) cut off and zinc serum levels among all subjects in this study were <65 μg/dl. There were 47.1% stunting children found in this study. Mean zinc serum levels significantly differences between dietary zinc quintile (p=0.000) and between stunting status (p=0.000). At risk inadequate dietary zinc still contributed to zinc deficiency in coastal school children population. Zinc status was significantly different between stunted and normal children.Keywords: coastal area, dietary zinc, EAR, stunting, zinc serum levels